Redesign Formulir Informed Consent at Jimmy Medika Mother & Child Hospital Borneo - Ulia Fitri; Suwanto Suwanto; Muhammad Rafli Aidilllah (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
Informed consent is the process by which a person understands relevant information about a medical procedure or procedure. This research is in the form of designing a medical record formular based on the principle of informed consent that facilitates health services. This type of research is A qualitative descriptive study that analyzes the design of forms from anatomical, physical and substantive aspects of informed consent forms. The medical procedure consent form is a form that must be owned by every health care facility that regulates the agreement between the patient/patient's family and the doctor or health worker. RSIA Jimmy Medika Borneo has implemented a good design in the approval of medical procedures but there are several things that must be redesigned including the preliminary section and the approval and closing section. Recommendations for Jimmy Medika Borneo Hospital to evaluate through management review meetings including evaluating services and medical support documents so that service procedures are in accordance with the policies that have been regulated.